Nanostructured Dielectric Layer for Ultrathin Crystalline Silicon Solar Cells - Yusi Chen; Yangsen Kang; Jieyang Jia; Yijie Huo; Muyu Xue; Zheng Lyu; Dong Liang; Li Zhao; James S. Harris (International Journal of Photoenergy)
Nanostructures have been widely used in solar cells due to their extraordinary photon management properties. However, due to poor pn junction quality and high surface recombination velocity, typical nanostructured solar cells are not efficient compared with the traditional commercial solar cells. Here, we demonstrate a new approach to design, simulate, and fabricate whole-wafer nanostructures on dielectric layer on thin c-Si for solar cell light trapping. The optical simulation results show that the periodic nanostructure arrays on dielectric materials could suppress the reflection loss over a wide spectral range. In addition, by applying the nanostructured dielectric layer on 40 μm thin c-Si, the reflection loss is suppressed to below 5% over a wide spectra and angular range. Moreover, a c-Si solar cell with 2.9 μm ultrathin absorber layer demonstrates 32% improvement in short circuit current and 44% relative improvement in energy conversion efficiency. Our results suggest that nanostructured dielectric layer has the potential to significantly improve solar cell performance and avoid typical problems of defects and surface recombination for nanostructured solar cells, thus providing a new pathway towards realizing high-efficiency and low-cost c-Si solar cells.